Fatwa Institutions in Handling Religious Blasphemy Crimes in Indonesia and Malaysia - Ilahi, M. Ridho; Irfan, M. Nurul; Kamarusdiana, Kamarusdiana; Hidayatulloh, Hidayatulloh; Zulfa, Eva Achjani (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2024)
The position of fatwa institutions in cases of blasphemy by cult groups is often seen as representing only the majority Muslims and blaming minority Muslims, as in Indonesia, or seen as a tool to suppress anti-government groups, as in Malaysia. This study aims to explain the position of the Indonesian Ulema Council (MUI) and Jawatankuasa Fatwa in handling heresy, including the reasons behind the differences in the positions and roles of the two institutions. Researchers use qualitative methods with a comparative legal approach. This study found that MUI's heretical fatwas had no legal force, the central MUI has the authority to enact heretical fatwas within MUI institutions, but not absolutely to respond to national laws, and not play a role in the criminal justice system. Meanwhile, Jawatankuasa Fatwa Kebangsaan (JFK) has the force of law with certain conditions, however, the federal state Jawatankuasa Fatwa has the authority to determine heretical fatwas to respond and strengthen state regulations (blasphemy laws). This research can be used as a reference for law enforcement in handling blasphemy cases by considering the views of MUI and Jawatankuasa Fatwa, which are regulated adequately by laws and regulations.